2001
DOI: 10.1046/j.1471-4159.2001.00206.x
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidative stress selectively down‐regulates the neuronal stress response activated under conditions of endoplasmic reticulum dysfunction

Abstract: Oxidative stress has been implicated in mechanisms leading to neuronal cell injury in various pathological states of the brain. Here, we investigated the effect of peroxide exposure on the expression of genes coding for cytoplasmic and endoplasmic reticulum (ER) stress proteins. Primary neuronal cell cultures were exposed to H 2 O 2 for 6 h and mRNA levels of hsp70, grp78, grp94, gadd153 were evaluated by quantitative PCR. In addition, peroxide-induced changes in protein synthesis and cell viability were inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 63 publications
4
36
0
Order By: Relevance
“…GRP78 and GRP94 (78 and 94 kDa glucoseregulated proteins) are two endoplasmic reticulumlocated molecular chaperones that participate in the antioxidative stress response (39,40). In this study, we measured both GRP78 and GRP94 protein levels in Pb and/or Cu-exposed astroglia.…”
Section: Resultsmentioning
confidence: 99%
“…GRP78 and GRP94 (78 and 94 kDa glucoseregulated proteins) are two endoplasmic reticulumlocated molecular chaperones that participate in the antioxidative stress response (39,40). In this study, we measured both GRP78 and GRP94 protein levels in Pb and/or Cu-exposed astroglia.…”
Section: Resultsmentioning
confidence: 99%
“…Less is known about the regulation of SERCA activity in brain, where it occurs at much lower levels than in muscle (41), but a number of studies, mainly using thapsigargin, have shown that SERCA plays a crucial role in neuronal function. For instance, exposure of neurons and neuronal cell lines to thapsigargin results in ER stress (42,43), decreased neuronal viability (8, 9), inhibition of protein synthesis (44), and injury in developing nerves (45).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in parkin mRNA levels of cultures exposed to Tg were evaluated by quantitative PCR as described (19,20). The following parkin primers were used: (sequence taken from GenBank, accession no.…”
Section: Methodsmentioning
confidence: 99%